Formulation and evaluation of Lip Scrub preparation from lemon peel extract Citrus Limon (L.) Osbeck - Niati Ambarsari; La Malihi; Nur Fadilah (PT. Anagata Sembagi Education, 2025)
Dry and chapped lips are a common disorder of the lips. Common causes of dry and chapped lips are damage to keratin cells due to sunlight and dehydration. This research aims to determine the physical properties of lip scrub preparations from lemon peel (Citrus limon L.) Osbeck and which concentration is the best. This research method was carried out experimentally, namely making extracts using the maceration method, then formulating lip scrub preparations with varying extract concentrations and physical stability testing which included organoleptic, homogeneity, pH and spreadability tests. The results obtained in this research, namely the organoleptic test evaluation, were light brown in color, had the smell of oleum ricini, and had a bitter sweet taste and semi-solid form. Homogeneity test to determine the homogeneity of the lip scrub preparation with the absence of lumpy materials that are not dissolved. The pH test obtained was a semi-solid lip scrub preparation that was stable, namely at an average pH of 5.5. The spreading power test obtained a diameter of 4-5 cm. Based on the evaluation results, lip scrub preparations that have good and stable physical quality are F3 with a lemon peel extract concentration of 6%.